2020
DOI: 10.1002/gj.3780
|View full text |Cite
|
Sign up to set email alerts
|

Geologically controlled intermittent gas eruption and its impact on bottom water temperature and chemosynthetic communities—A case study in the “HaiMa” cold seeps, South China Sea

Abstract: In 2018, the Institute of Deep Sea Science and Engineering investigated the “HaiMa” cold seeps in the northwestern part of the South China Sea using R/V “TanSuoYiHao” with manned submersible “ShenHaiYongShi.” Ten dives were conducted to make seafloor observations at six cold seeps (HM‐1 to HM‐6). By combining multibeam echosounder data and seismic profiles, a systematic study was made to understand fluid migration, accumulation, and eruption and their impact on the ecosystem. Location of gas flares observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 48 publications
(61 reference statements)
0
25
0
Order By: Relevance
“…It has been suggested that the physical properties of gas hydrate-bearing sediments are closely related to the gas hydrate saturation and effective confining stress [24,26]. In addition, gas hydrate layers and veins have been discovered in marine sediments in marine sea areas, which can change the marine sediments from isotropic to anisotropic materials [47,48]. This inhomogeneity of the material properties increases the difficulty of predicting the stability of the seabed sediments during gas hydrate production [38].…”
Section: Factors Controlling the Physical Properties Of Gasmentioning
confidence: 99%
“…It has been suggested that the physical properties of gas hydrate-bearing sediments are closely related to the gas hydrate saturation and effective confining stress [24,26]. In addition, gas hydrate layers and veins have been discovered in marine sediments in marine sea areas, which can change the marine sediments from isotropic to anisotropic materials [47,48]. This inhomogeneity of the material properties increases the difficulty of predicting the stability of the seabed sediments during gas hydrate production [38].…”
Section: Factors Controlling the Physical Properties Of Gasmentioning
confidence: 99%
“…Therefore, unlike hydrothermal systems, which are mainly distributed in mid-ocean ridges [4,5], cold seeps are widely dispersed throughout the active and passive continental margins and sedimentary basins with thick sediments [3,[6][7][8]. Methane reacts with seawater sulfate via the sulfate-driven anaerobic oxidation of methane (SR-AOM), which produces hydrogen sulfide and bicarbonate [9], and provides nutrients for chemosynthetic communities [10][11][12]. Therefore, a special chemosynthetic ecosystem [13], widely distributed carbonate on the seafloor [14], and gas bubble emission from the seafloor [15,16] are important indicators for the identification of marine cold seeps.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, several active cold seeps have been discovered on the northern slope of the South China Sea [31], including the Jiulong seeps [32], Haima cold seeps [10], and station F [33]. In recent years, a large number of seep carbonates have been collected from these cold seeps by multiple research expeditions [30][31][32]34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cold seeps is one of the extreme deep-sea environments, where fluid migrates upward from deep stratum to the seafloor under pressure that result from plate subduction or gravity compression [17][18][19]. It mostly occurs in geologically active and passive continental margins and trenches [19].…”
Section: Introductionmentioning
confidence: 99%